MO728: Association of Interleukin-6 with Subendocardial Viability Ratio in Haemodialysis Patients. (3rd May 2022) - Ekart, Robert; Piko, Nejc; Vodošek Hojs, Nina; Stropnik Galuf, Tina; Hren, Martin; Zorman, Tadej; Hojs, Radovan
Abstract: BACKGROUND AND AIMS: Inflammation is an important process in the pathogenesis of atherosclerosis, and chronic kidney disease (CKD) is recognized as a proinflammatory state. Interleukin-6 (IL-6) is associated with cardiovascular events and also predicts mortality in individuals with CKD patients. The subendocardial viability ratio (SEVR) is one of the pulse wave analysis parameters and represents a non-invasive measure of coronary perfusion. In a non-dialysis CKD population, we previously reported about the prognostic value of SEVR for cardiovascular outcome in these patients. The aim of this study was to investigate the association between inflammatory markers IL-6, tumour necrosis factor-α (TNF-α), high-sensitive C-reactive protein (hsCRP) and SEVR in CKD patients undergoing maintenance hemodialysis (HD). METHOD: In a cross-sectional study, we enrolled only HD patients. SEVR was assessed using a generalized transfer function applied to the radial artery pressure wave form (Sphygmocor, Atcor Medical, Sydney, Australia). Plasma IL-6, TNF-α and hsCRP were measured by an enzyme-linked immunosorbent assay. RESULTS: A total of 40 HD patients (mean age 65.2 ± 11.8 years, 72.5% male) were included. Other descriptive parameters are presented in Table 1. A statistically significant correlation was found between SEVR and IL-6 ( r = 0.379; P = 0.016), but not between SEVR and TNF-α (P = 0.195), nor between SEVR and hsCRP (P = 0.686). In a multivariate adjusted model with SEVR as dependent variable and IL-6, TNF-α and hsCRP as independent variables we found a statistically significant association only between SEVR and IL-6 (β = 0.393; P = 0.017). CONCLUSION: This study suggests an association between IL-6 and SEVR in HD patients.